A case study of network neutrality in Korea - Dong-Hee Shin (International Telecommunications Society (ITS), 2012)
This study investigates the network neutrality issue in Korea by focusing on the debates among the stakeholders. It examines the dynamic discussions of the issues by identifying how diverse groups of stakeholders are affected by various actions taken by the emergence of network neutrality. It also presents a quantitative analysis that reveals the factors implicated in the net neutrality debate and statistically significant differences among individuals on opposite sides of the debate. A qualitative analysis reveals insights into the connection between specific factors and positions in the net neutrality debate. The findings show that the issue of net neutrality is not only complicated, but also as complex as the parties' diverse interests. The paper concludes that a careful combination of government intervention and market forces is an effective way to govern net neutrality.
Keywords: 330; Network neutrality; stakeholder analysis; web of stakeholders